STRATEGI PENANAMAN AKHLAK MELALUI CERITA BERGAMBAR PADA SISWA KELAS AWAL SEKOLAH DASAR - - Rakimahwati (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2012)
Abstract: The purpose of this classroom action research was to improve students' character using pictured story, especially in understanding a good or a bad behaviour.The subjects were 20 students of lower grade elementary schools' students at Padang city. Data was collected by observation, interview, and product. The collected Data was analyzed using a precentage technique.Result of this research showed there were improve of students' character. Based on the result, it can reccomended for the lower grade elementary schools' teachers teach the good character and Islami in the multiple subjects. Abstrak: Penelitian tindakan kelas ini bertujuan untuk meningkatkan akhlak siswa melalui cerita bergambar, khususnya dalam memahami tingkah laku baik dan buruk. Subyek penelitian terdiri atas 20 peserta didik SD kelas awal di Kota Padang. Data dikumpulkan melalui observasi, wawancara, dan hasil karya. Pengolahan data menggunakan teknik presentase. Hasil penelitian menunjukkan adanya peningkatan akhlak siswa. Berdasarkan hasil penelitian tersebut dapat disarankan bagi guru sekolah dasar kelas awal agar senantiasa menanamkan akhlak yang baik dan islami pada berbagai mata pelajaran.